Acanthosis Nigricans Associated with Morbid Obesity and Colorectal Adenocarcinoma. (26th March 2012) - Li, J.; Yazdabadi, A.; Sinclair, R.
Abstract : We report a case of a morbidly obese 32-year-old man presenting with acanthosis nigricans in the setting of Duke's B adenocarcinoma of the hepatic flexure.